THE SPECIFICS OF ISCHEMIC HEART DISEASE MANAGEMENT IN ELDERLY - F. I. Belyalov (Российский кардиологический журнал)
Ischemic heart  disease impacts  greatly the morbidity and mortality of population. The  article  focuses   on  the  specifics  of  diagnostics   and  treatment of  chronic coronary heart disease in patients of older age. Management of this kind of patients is complicated  with comorbidity, cognition decline, increased risk of side effects, reduced range of treatment options.